The Behaviour of the Third Age towards the Recycling of printed paper in the Region of Attica. Case Study: The Municipalities of Egaleo and Chaidari. - Passas, Xenophontas; Mitoula, Roido; Sardianou, Eleni; Theodoropoulou, Eleni (Archives of Business Research, 2019)
The purpose of this thesis is to examine the determinant factors of recycling and in particular of paper recycling. The research focuses on paper recycling behaviour on the part of the elderly in the Region of Attica. Primary research was based on the use of layered data. The survey data were collected through the distribution of questionnaires to senior citizens in the municipalities of Egaleo and Chaidari. The questionnaire was given hand by hand in the region’s Open Care Center for the Elderly (OCCE) during the period from November 2017 until February 2018 (11/2017 - 02/2018). The final sample of the survey amounted to 375 participants. Through multiple linear regressions, behaviour towards paper recycling seems to be affected by the intention to recycle, subjective patterns, perceived behavioural control, moral standards, educational level, monthly family income and monthly pension. Similarly, an increased intention to recycle paper is associated with higher values of the scale of recycling behaviour. Regarding the socio-demographic data of the participants, the participants who are graduates of post-secondary education show a lower score on the recycling behavior scale than the graduates of Primary school. Participants with a monthly family income of between € 800 and € 1500 have a lower score on the recycling behaviour scale than those with a monthly family income of less than € 800.